Orbital T-Cell Lymphoma with Discrete Enlargements of All Extraocular Muscles Bilaterally in Patient with Moon Face Countenance - Hideaki Kawakami; Kiyofumi Mochizuki; Hideko Goto; Naoki Watanabe; Takuji Tanaka (Case Reports in Ophthalmological Medicine)
Purpose. To report our findings in a case of orbital T-cell lymphoma in which all of the extraocular muscles (EOMs) were bilaterally and discretely enlarged and the patient had a moon face countenance. Case. A 59-year-old woman presented with visual disturbances in her left eye, hyperemia in both eyes, and a moon face countenance. Examinations showed limited upward gaze in the right eye, blepharoptosis, hypertropia, and limited downward and rightward gaze in the left eye. Slit-lamp examination showed only chemosis and hyperemia of both eyes. Magnetic resonance imaging with contrast revealed discrete enlargements of the muscle bellies in all EOMs without abnormalities of the orbital fat in both eyes. Blood examinations excluded thyroid- and IgG4-related ophthalmopathy, and EOM biopsy revealed peripheral T-cell lymphoma. After beginning aggressive chemotherapy, the enlarged EOMs, limited eye motility, and moon face countenance improved. Unfortunately, the patient died of sepsis during the chemotherapy. Conclusions. A lymphoma should be included in the differential diagnosis of eyes with enlarged EOMs. Because lymphomas can lead to death, it is important for clinicians to consider lymphomas in eyes with enlarged EOMs.